2022
DOI: 10.1186/s12877-022-03298-8
|View full text |Cite
|
Sign up to set email alerts
|

Sleep duration, genetic susceptibility, and Alzheimer's disease: a longitudinal UK Biobank-based study

Abstract: Background Alzheimer's disease (AD) is the most frequently occurring type of dementia. Concurrently, inadequate sleep has been recognized as a public health epidemic. Notably, genetic and environmental factors are now considered contributors to AD progression. Objective To assess the association between sleep duration, genetic susceptibility, and AD. Methods and results Based on 483,507 participants fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 51 publications
0
11
1
Order By: Relevance
“…Our findings provide a new line of evidence in favour of the potential role of sleep duration in Alzheimer's disease risk. These findings contrast with multiple previously published MR studies that did not find evidence for an association between sleep duration and Alzheimer's disease [6][7][8]31,32]. However, statistical power is notably limited in MR studies given the low variance explained by the genetic instruments used to predict sleep duration.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…Our findings provide a new line of evidence in favour of the potential role of sleep duration in Alzheimer's disease risk. These findings contrast with multiple previously published MR studies that did not find evidence for an association between sleep duration and Alzheimer's disease [6][7][8]31,32]. However, statistical power is notably limited in MR studies given the low variance explained by the genetic instruments used to predict sleep duration.…”
Section: Discussioncontrasting
confidence: 93%
“…Thus far, GWAS have identified few single-nucleotide polymorphisms (SNPs) for device-derived sleep duration [4,5], which explain limited trait variance (0.33%) [4]. Given GWAS sample sizes (n~91,000) and the limited variation explained by previously identified significant SNPs, investigation of sleep duration and dementia risk using Mendelian randomisation (MR) may be underpowered, as reflected by the wide confidence intervals around the estimates in previous studies [6][7][8]. We have previously reported that up to 18% of the phenotypic variance could be explained by common SNPs (P<5-e-3) [4], so we hypothesise that a PGS based on this wider range of genetic variants may increase power to better investigate the role of sleep duration in dementia risk.…”
Section: Introductionmentioning
confidence: 99%
“…We found a discrepancy between self-reported and PSG-measured sleep duration in those who developed NDDs, with shorter objective TST and longer reported sleep duration. Previous observational and Mendelian randomized studies showed an association between prolonged self-reported sleep duration and incident dementia 35, 36 . These and our findings emphasize the need for objective sleep efficiency and duration measures.…”
Section: Discussionmentioning
confidence: 91%
“…There are many risk factors for the development of cognitive impairment in older adults; for example, excessive sleep duration increases the risk after adjusting for numerous relevant risk factors (Yuan et al, 2022a ), and those with a low BMI (< 23 kg/m 2 ) have a higher risk of developing dementia (Yuan et al, 2022b ). With the advent of an aging society, cognitive impairment occurrence will become more common (Afzal et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%